Fulfillment of Clean Water Needs in Tamangil Nuhuten Village with Addition of New Spring - Paschal Rumihin; Soebagio Soebagio (UKaRsT, 2023)
Seventy-two million Indonesians have difficulty accessing clean water, especially in rural communities. This causes various diseases and has an impact on people's welfare. Currently, the community's need for clean water in Tamangil Nuhuten Village depends on the Wiak spring and often experiences shortages. This research aims to analyze the need and availability of clean water in Tamangil Nuhuten Village. The need for clean water is calculated using water consumption data and the projected population. As for water availability, the water source discharge data is collected from the government and measures the water discharge directly to validate the data. It is necessary to analyze the water balance to determine the ability to meet the demand for clean water. The results showed that the need for clean water for the next 10 years is 2.0 liters/second, while the water supply is 1.06 liters/second, so it is still insufficient. Fulfillment can be done by adding the Baluruk spring 1.8 km away. Baluruk Spring can discharge of 83.3 liters/second with constant conditions throughout the year and meets clean water quality. Intake of clean water can be done by building two reservoirs to reduce the sediment content with dimensions of 4m x 6m x 3m, which are placed 500m from the village. As well as used two 6-inch pipes for transmission pipes and one 4-inch pipe for distribution. Thus the water needs of the Tamangil Nuhuten Village community can be fulfilled until 2031.